STRATEGIC MAP AS A COMPONENT OF THE COMPANY'S MARKETING STRATEGY - VOVK, Volodymyr; HAVRYLCHENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The purpose of the study is to develop recommendations for the effective use of the strategic map as a marketing strategy tool to improve its flexibility, adaptability and effectiveness in modern market conditions. The role of the strategic map as an important element of the enterprise's marketing strategy is considered. In particular, the functions of the strategic map in the context of marketing, as well as approaches to development and implementation, are explored. The main components of the strategic map are analyzed: financial, customer, internal processes and the perspective of training and development. A typical model of a strategic map with the use of key indicators is presented, which takes into account potential perspectives and directions of development affecting the strategic potential of the organization. The proposed model provides a holistic vision of long-term goals and allows to adapt to changes in the external environment, supporting the competitiveness of the enterprise; integrates indicators contributing to the improvement of the efficiency of internal processes, personnel development and improvement of the client-oriented strategy, which makes it a universal tool for strategic management. It has been proven that the implementation of a strategic map helps to increase consistency between departments, improve communication and create a unified system for evaluating achievements. Recommendations are given for increasing the efficiency of using the strategic map in the conditions of a changing market environment.
Keywords: strategy; strategic map; marketing; marketing tools; marketing strategy; marketing strategic activity